Pharmacodynamics of rituximab on B lymphocytes in paediatric patients with autoimmune diseases. Issue 8 (20th June 2019) - Pan, Shan; Yu, Huixin; Surti, Ayesha; Cheng, Iek; Marks, Stephen D.; Brogan, Paul A.; Eleftheriou, Despina; Standing, Joseph F.
Abstract : Aims: Rituximab is a chimeric IgG‐1 monoclonal antibody that depletes B cells, aiding in the treatment of several conditions including autoimmune diseases. It is not licensed for use in children. This study aimed to quantify the B cell‐related pharmacodynamics of rituximab in children with autoimmune disease. Methods: Routine electronic health record data were collected at a large paediatric tertiary hospital in London, UK. Dosing protocols were either 2 × 750 mg/m 2 intravenous infusions of rituximab on days 1 and 15, or 4 × 375 mg/m 2 infusions on days 1, 8, 15 and 22. Rituximab pharmacokinetics (PK) were not measured but CD19+ lymphocyte counts were taken before and after rituximab treatment. A dose–response model was constructed describing the life cycle of CD19+ lymphocytes, with rituximab assumed to increase the death rate. Rituximab effect was assumed to decay by first‐order kinetics. Results: In total, 258 measurements of CD19+ lymphocyte counts were collected from 39 children with 8 autoimmune diseases. The elimination rate constant (% relative standard error) of rituximab effect decay was 0.036 (22.7%) days −1 and CD19+ turnover was 0.02 (41%) days −1 corresponding to half‐lives of 19 and 35 days respectively. Rituximab increased CD19+ death rate 35‐fold, with methotrexate and cyclophosphamide associated with further increases. Simulations suggested that a single infusion of 750 mg/m 2 provides similar 6‐month suppression of CD19+ lymphocytes to current dosing. Conclusions: Rituximab pharmacodynamics (PD) in paediatric autoimmune diseases has been described. Compared with rituximab alone, the additional effect of methotrexate or cyclophosphamide was statistically significant but small.